Factors associated with the adoption of e-wallets among students / Nurin Jaslina binti Jasmin ... [et al.] - Jasmin, Nurin Jaslina; Jaafar, Farizah Syahirah; Bahrin, Ani Juaini; Tamsin, Nowyannie Willie D. (Universiti Teknologi MARA, Sabah, 2022)
With the advent of new technology, Malaysia is now experiencing an enormous activities in the usage of digital payments for good and services especially for financial transactions. Several shoppers around the world are now preferring cashless transactions when they go for daily shopping. This has led to the implementation of online transactions as payment tools which can be illustrated through the existence of credit cards, debit cards, and e-wallets payments. Generally, e-wallets act as a new financial transaction in a digital platform that holds the same functions as a traditional wallet. As internet users are growing rapidly day by day, this indicates the adoption of e-wallets will become more popular, especially among young generations. It is easier for the young generation such as the students to adapt well to technological advancement due to their ability and acceptance of today's trends. Therefore, this study aims to investigate the factors associated with e-wallet adoption among students. The current work utilized an extended version of the Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT) to analyze the variables in this study. Three variables were identified as the factors that influence the adoption of e-wallets among students: Perceived Usefulness (PU), Perceived Ease of Used (PEOU), and Social Influences (SI). Results from the current work indicated that PU, PEOU, and SI are associated with e-wallet adoption among students. Significantly, the government played an important role in influencing people's adoption by creating incentives and implementing policies. Hence, the government may also take part in enhancing the business industry on e-commerce towards e-wallet adoption.